Efficiency and Effectiveness Analysis of a Digital Road Problem Reporting Platform: A Simulation Study Using MATLAB with Applications to the "MyCity" Platform - Ali Hassien Mohamed Milad; Awatef Salem Ibrahim Ibrahim; Rabia Ali Alkhazmi (Journal of Scientific and Human Dimensions, 2025)
This study aims to evaluate the performance of electronic platforms for reporting urban infrastructure issues, with a focus on road problem reporting systems. An integrated simulation model was developed using the MATLAB environment to simulate the operational processes of the virtual "MyCity" platform, while analyzing the impact of intelligent scheduling systems on key performance indicators. The results showed that implementing a dynamic priority-based scheduling system can improve average response times by 35.7%, increase task completion rates within target timeframes by 28.3%, and enhance resource utilization efficiency by 42.1% compared to traditional systems. The study presents a methodological framework applicable to real urban reporting systems and proposes practical improvements to enhance the effectiveness of municipal services.